Impacts of energy-efficiency investments on internal conditions in low-income households. Issue 6 (18th August 2018) - Poortinga, Wouter; Jiang, Shiyu; Grey, Charlotte; Tweed, Chris
ABSTRACT: Living in cold conditions poses a risk to health, in particular to low-income, fuel-poor households. Improving the energy efficiency of the housing stock may bring multiple positive health gains through improved indoor temperatures and reduced fuel consumption. This study used a multilevel interrupted time-series approach to evaluate a policy-led energy-performance investment programme. Long-term monitoring data were collected for intervention and control households at baseline ( n  = 99) and follow-up ( n  = 88), creating a dataset with 15, 771 data points for a series of daily-averaged hydrothermal outcome variables. The study found that the intervention raised indoor air temperature by on average 0.84 K as compared with control households, thereby bringing the majority of indoor temperature measurements within the 'healthy' comfort zone of 18–24°C, while average daily gas usage dropped by 37%. External wall insulation was the most effective measure to increase indoor air temperature. The greatest increases were found in the evening and at night, in the bedroom, and in British steel-framed buildings. No evidence was found that the intervention substantially increased indoor relative humidity levels when accompanied by mechanical ventilation. The study concludes that the multilevel interrupted time-series approach offers a useful model for evaluating housing improvement programmes.